2009
DOI: 10.1093/toxsci/kfp179
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative and Oxidative Stress in Toxicology and Disease

Abstract: Persistent inflammation and the generation of reactive oxygen and nitrogen species play pivotal roles in tissue injury during disease pathogenesis and as a reaction to toxicant exposures. The associated oxidative and nitrative stress promote diverse pathologic reactions including neurodegenerative disorders, atherosclerosis, chronic inflammation, cancer, and premature labor and stillbirth. These effects occur via sustained inflammation, cellular proliferation and cytotoxicity and via induction of a proangiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 73 publications
2
159
0
1
Order By: Relevance
“…Several studies have reported that oxidative stress plays a central role in disease pathogenesis and in tissue damage in response to toxicant exposures (Roberts et al, 2009). For example, Koyu et al (2006) showed that cadmium has an important toxic effect on liver tissue and concluded that cadmium exhibits its toxicity by increasing lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that oxidative stress plays a central role in disease pathogenesis and in tissue damage in response to toxicant exposures (Roberts et al, 2009). For example, Koyu et al (2006) showed that cadmium has an important toxic effect on liver tissue and concluded that cadmium exhibits its toxicity by increasing lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress occurs when an excess of reactive oxygen species (ROS) are generated from any of a variety of sources, including the mitochondrial electron transport chain and reduced nicotinamide adenine dinucleotide phosphate (NAD(P)H) oxidases. ROS can damage macromolecules and activate signaling pathways that include a number of inflammatory mediators [43,44]. Inflammation, in turn, can lead to further oxidative stress in a cycle that contributes to the progression of many diseases.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Inflammation, in turn, can lead to further oxidative stress in a cycle that contributes to the progression of many diseases. Atherosclerosis, diabetes mellitus, chronic obstructive pulmonary disease, and cancer are examples of diseases associated with ROS-induced chronic inflammation [43,45,46]. Laboratory models suggest these diseases can either be prevented, treated, or cured through attenuating ROS, which may be achieved through treatment with resveratrol [22,47,48].…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…95 Curtis recently identified a number of oxidative stress and DNA repair proteins that are needed to prevent the accumulation of ROS and influence the estrogen-responsiveness of MCF-7 breast cancer cells, showing that these proteins may be differentially expressed in normal mammary tissue, DCIS, and IDC. 96 Some authors demonstrated that these oxidative stress proteins form an interactive network, acting collectively to regulate oxidative stress and maintain a functional cellular environment.…”
Section: Interactions Between Stromal and Tumor Epithelial Cellsmentioning
confidence: 99%